Preemption Games: Theory and Experiment - Anderson, Steven T; Friedman, Daniel; Oprea, Ryan (American Economic Review, 2010)
Several impatient investors with private costs C i face an indivisible irreversible investment opportunity whose value V is governed by geometric Brownian motion. The first investor i to seize the opportunity receives the entire payoff, V-C i . We characterize the symmetric Bayesian Nash equilibrium for this game. A laboratory experiment confirms the model's main qualitative predictions: competition drastically lowers the value at which investment occurs; usually the lowest-cost investor preempts the other investors; observed investment patterns in competition (unlike monopoly) are quite insensitive to changes in the Brownian parameters. Support is more qualified for the prediction that markups decline with cost. (JEL C73, D44, D82, G31)